A novel comparative study of crystalline perfection and optical homogeneity in Nd:GGG crystals grown by the Czochralski technique with different crystal/melt interface shapes. (10th November 2013) - Zimik, Khavangkhui; Bhagavannarayana, G.; Kumar, Ramesh; Chauhan, Rashmi Rai; Murari, Krishna; Malhan, Neelam; Thakur, Harneet V.
<x xml:space="preserve">Abstract</x> Nd:GGG crystals (GGG is gadolinium gallium garnet) grown with different crystal/melt interface shapes (convex/flat/concave) by varying the seed rotation rate while using the Czochralski technique were studied for their optical homogeneity and crystalline perfection by optical polarization microscopy (OPM) and high‐resolution X‐ray diffractometry (HRXRD), respectively. It was found that there is a remarkable effect of seed rotation rate, which decides the shape of the crystal/melt interface, on the optical homogeneity and crystalline perfection. It was found experimentally that, as the rotation rate increases, the crystal/melt interface changes from convex to flat. If the rate further increases the interface becomes concave. With a steep convex interface (for low rotation rates), certain facets are concentrated in the small central portion of the crystal, and as the rate increases, these facets slowly move outward, leading to improved optical homogeneity and crystalline perfection as observed from the OPM and HRXRD results. The strain developed in the crystalline matrix as a result of segregation of oxygen in the crystals at low seed rotation rates as observed from HRXRD seems to be the reason for the observed optical inhomogeneity. The correlation between optical inhomogeneity and crystalline perfection for a variety of specimens with different shapes of the crystal/liquid interface obtained at different seed rotation rates is reported.